2012
DOI: 10.1016/j.pain.2011.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Activation of descending pain-facilitatory pathways from the rostral ventromedial medulla by cholecystokinin elicits release of prostaglandin-E2 in the spinal cord

Abstract: Cholecystokinin (CCK) has been suggested to be both pro-nociceptive and anti-opioid by actions on pain modulatory cells within the RVM. One consequence of activation of RVM CCK2 receptors may be enhanced spinal nociceptive transmission but how this might occur, especially in states of pathological pain is unknown. Here, in vivo microdialysis was used to demonstrate that levels of RVM CCK increased by approximately 2-fold following ligation of L5/L6 spinal nerves (SNL). Microinjection of CCK into the RVM of naï… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 66 publications
(111 reference statements)
0
36
0
Order By: Relevance
“…Some studies have shown an increase of 5-HT levels in the dorsal spinal cord of rats submitted to spinal nerve injury (Wei et al, 2010;Marshall et al, 2012). Those results imply that nerve injury promotes the participation of the central serotonergic system that then leads to the increase of 5-HT levels at the spinal level.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Some studies have shown an increase of 5-HT levels in the dorsal spinal cord of rats submitted to spinal nerve injury (Wei et al, 2010;Marshall et al, 2012). Those results imply that nerve injury promotes the participation of the central serotonergic system that then leads to the increase of 5-HT levels at the spinal level.…”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that stimulation of spinal 5-HT 1A (Colpaert et al, 2004;Aira et al, 2010) and 5-HT 1B/1D (Kayser et al, 2002(Kayser et al, , 2011 receptors produces antiallodynic effects, whereas activation of spinal 5-HT 2 (Aira (Rahman et al, 2006;Chen et al, 2009;Wei et al, 2010;Marshall et al, 2012), 5-HT 4 and 5-HT 6 (Rocha-González, personal communication) and 5-HT 7 (Amaya-Castellanos et al, 2011) receptors instead elicits pronociceptive effects. Nevertheless, to the best of our knowledge, no study has investigated directly the role of spinal 5-HT 5A receptors in neuropathic pain models in rats.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…RVM sends projections to the spinal cord through the dorsolateral funiculus Burgess et al, 2002) which releases cholecystokinin, dynorphin, calcitonin gene-related peptide (CGRP) and serotonin (5-hydroxytriptamine, 5-HT), among other neurotransmitters, to promote development and maintenance of long-term nociception (Kovelowski et al, 2000;Gardell et al, 2003;Heinricher and Neubert, 2004;AmbrizTututi et al, 2011). It is thought that activation of RVM ON cells, by cholecystokinin, leads to behavioral allodynia and hyperalgesia (Kovelowski et al, 2000;Heinricher and Neubert, 2004;Xie et al, 2005;Marshall et al, 2012) and a time-dependent dynorphin A (Wagner et al, 1993;Laughlin et al, 1997;Malan et al, 2000;Burgess et al, 2002), cholecystokinin (Gustafsson et al, 1998;Xu et al, 2001;Kim et al, 2009) and 5-HT (Wei et al, 2010;Marshall et al, 2012) increase in the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of 5-HT in pain processing is complex as it may inhibit and/or facilitate nociceptive transmission depending on the type of nociceptive stimuli and the nature of the 5-HT receptors. In the case of the formalin test, it seems that serotonergic descending inhibition is important to develop primary hyperalgesia while descending facilitation participates in secondary hyperalgesia (Vanegas and Schaible, 2004 descending system is involved in the facilitation of the spinal nociceptive transmission (Suzuki et al, 2004;Wei et al, 2010;Leong et al, 2011;Marshall et al, 2012). For instance, spinal nerve ligation leads to a loss (one third) of serotonergic neurons (Leong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%